Looking queer: body image and identity in lesbian, bisexual, gay, and transgender communities - Atkins, Dawn (Haworth Press, 1998)
Looking Queer: Body Image in Lesbian, Bisexual, Gay, and Transgender Communities contains research, firsthand accounts, poetry, theory, and journalistic essays that address and outline the special needs of sexual minorities when dealing with eating disorders and appearance obsession. Looking Queer will give members of these communities hope, insight, and information into body image issues, helping you to accept and to love your body. In addition, scholars, health care professionals, and body image activists will not only learn about queer experiences and identity and how they affect individuals, but will also understand how some of the issues involved affect society as a whole. Dismantling the myth that body image issues affect only heterosexual women, Looking Queer explores body issues based on gender, race, class, age, and disability. Furthermore, this groundbreaking book attests to the struggles, pain, and triumph of queer people in an open and comprehensive manner. More than 60 contributors provide their knowledge and personal experiences in dealing with body image issues exclusive to the gay and transgender communities, including: exploring and breaking down the categories of gender and sexuality that are found in many body image issues finding ways to heal yourself and your community discovering what it means to “look like a dyke” or to “look gay” fearing fat as a sign of femininity determining what race has to do with the gay ideal discussing the stereotyped ”double negative”–being a fat lesbian learning strategies of resistance to societal ideals critiquing ”the culture of desire” within gay men’s communities that emphasizes looks above everything else Revealing new and complex dimensions to body image issues, Looking Queer not only discusses the struggles and hardships of gay, lesbian, bisexual, and transgendered persons, but looks at the processes that can lead to acceptance of oneself. Written by both men and women, the topics and research in Looking Queer offer insight into the lives of people you can relate to, enabling you to learn from their experiences so you, too, can find joy and happiness in accepting your body.
Section: li, 467 p
Keywords: LGBTQIA2+; amériques; anthropologie; approches et analyses; cours; discipline; image corporelle; intersectionnalité; premier cycle; queer; régions géographiques; sciences humaines; soc2014; thématiques; troubles alimentaires; états-unis

Privilege: Expanding on Marilyn Frye's "Oppression" - Bailey, A. (JOURNAL OF SOCIAL PHILOSOPHY -AUGUSTA-, 1998)
This essay serves as both a response and embellishment of Marilyn Frye's now classic essay " Oppression." It is meant to pick up where this essay left off and to make connections between oppression, as Frye defines it, and the privileges that result from institutional structures. This essay tries to clarify one meaning of privilege that is lost in philosophical discussions of injustice. I develop a distinction between unearned privileges and earned advantages. Clarifying the meaning of privilege as unearned structural advantage makes visible the role white privilege plays in maintaining complex systems of domination such as racism, sexism, heterosexism and classism. Using a critical reading of both Frye and Young's accounts of oppression as a springboard, I develop a definition of privilege as a particular class of unearned advantages. -/- I distinguish my account of privilege from standard legal and philosophical definitions of privilege. The general distinction I make between privileges and advantages rests on three interrelated claims: that benefits granted by privilege are always unearned and conferred systemically to members of dominant social groups; that privileges granted to members of dominant groups solely on the basis of their membership in these groups is never justifiable; and, that privileges have an unconditional value that can be explained not only in terms of immunities, but also in terms of additional benefits
Keywords: 1900-1999; 1990-1999; amérique du nord; amériques; approches et analyses; cours; cycles supérieurs; discipline; discours dominant; fem9000; justice sociale; phi4336; philosophie; premier cycle; privilèges; périodes historiques; régions géographiques; sciences humaines; systèmes d'oppressions; thématiques; états-unis

Des droits à reconnaître: les lesbiennes face à la discrimination - Bonneau, Micheline; Demczuk, Irène (Les éditions du remue-ménage, 1998)
Regroupant recherches et analyses, témoignages et récits personnels, ce livre rend compte de la discrimination vécue par les lesbiennes. Malgré que le Québec ait adopté une Charte des droits de la personne qui interdit toute discrimination basée sur l'orientation sexuelle, il faut reconnaître que l'adoption de ce principe d'équité n'a pas fait disparaître toute trace d'hétérosexisme dans la société. Les lesbiennes ne bénéficient pas encore d'une égalité juridique formelle, encore moins réelle.
Section: 214 pages ; 23 cm
Keywords: 1900-1999; 1970-1979; 1980-1989; 1990-1999; LGBTQIA2+; amérique du nord; amériques; approches et analyses; canada; cours; discipline; discours dominant; droits des femmes*; hétéronormativité; hétérosexisme; identités LGBTQIA2+; inégalités; lesbianisme; lesbophobie; premier cycle; périodes historiques; queer; québec; régions géographiques; sciences humaines; sexualité; shm4000; soc2014; sociologie; systèmes d'oppressions; thématiques; violences

L'histoire... des femmes - Fournier, Pierre (De lutte en turlutte : une histoire du mouvement ouvrier québécois à travers ses chansons, 1998)
Keywords: amérique du nord; amériques; canada; chanson; discipline; histoire; histoire des femmes*; militance; québec; régions géographiques; sciences humaines; thématiques

La marche des femmes - Fournier, Pierre (De lutte en turlutte : une histoire du mouvement ouvrier québécois à travers ses chansons, 1998)
Keywords: amérique du nord; amériques; canada; chanson; discipline; histoire; militance; québec; régions géographiques; sciences humaines; thématiques; travail

La victoire des Midinettes - Fournier, Pierre (De lutte en turlutte : une histoire du mouvement ouvrier québécois à travers ses chansons, 1998)
Keywords: amérique du nord; amériques; canada; chanson; discipline; histoire; militance; québec; régions géographiques; sciences humaines; thématiques; travail

Le mouvement féministe des années 1970 - Fournier, Pierre (De lutte en turlutte. Une histoire du mouvement ouvrier québécois à travers ses chansons, 1998)
Keywords: 1900-1999; 1970-1979; amérique du nord; amériques; canada; chanson; discipline; histoire; militance; mouvements féministes; périodes historiques; québec; régions géographiques; sciences humaines; thématiques

Solidarité, mes frères et mes sœurs - Fournier, Pierre (De lutte en turlutte : une histoire du mouvement ouvrier québécois à travers ses chansons, 1998)
Keywords: amérique du nord; amériques; canada; chanson; discipline; histoire; militance; québec; régions géographiques; sciences humaines; thématiques

Female masculinity - Halberstam, Jack (J.) (Duke University Press, 1998)
Dans cet ouvrage essentiel de la théorie queer, Jack Halberstam s’attaque au statut protégé de la masculinité masculine et montre que la masculinité féminine lui offre une alternative distincte depuis plus de deux siècles. Démontrant que la masculinité féminine n’est pas une mauvaise imitation de la virilité, mais une mise en scène vivante et dramatique de genres hybrides et minoritaires, Halberstam catalogue la diversité des expressions de genre chez les femmes masculines, depuis les pratiques pré-lesbiennes du XIXe siècle jusqu’aux performances contemporaines des drag kings.
Keywords: amériques; approches et analyses; cours; discipline; fem1000; histoire; identités LGBTQIA2+; personnes trans*; premier cycle; queer; régions géographiques; sciences humaines; thématiques; états-unis

La contribution des femmes à l’histoire de la musique au Québec - Lefebvre, Marie-Thérèse (New Sound, 1998)
Lors d'un colloque international sur les femmes et la création musicale organise par I'Unesco en mars 1996, Mme Zaimont et Mme Ostleitner des Etats-Unis et de I'Autriche, ont démontre dans leur conférence respective á quel point la vie musicale des pays qu'elles représente est encore puissamment dominée par les forces conservatrices et traditionnelles I'Autriche plie sous le poids d'un héritage musical ancestral alors que les Etats-Unis (et jusqu'a un certain point le Canada anglophone) vit actuellement au rythme des tendances politiques de droite. Plusieurs des acquis du mouvement féministe sont actuellement remis en question dans les milieux décisionnels et on ne peut que s'inquiéter de I' impact que pourraient avoir ces mouvements conservateurs sur la création musicale des femmes de ce pays. Mais dans ce même colloque, nous avons également pu entendre les propos de représentantes d'autres pays, je pense ici a la Corée au Japon, a la Bolivie, a I'Uruguay ou les femmes prennent une place de plus en plus importante dans le discours musical et dans la production artistique. De son cote, Le Québec, peut-être a cause de sa situation linguistique et culturelle minoritaire, a développe au cours de son histoire une vitalité artistique enviable et a été a I'avant-garde dans plusieurs domaines dont la création musicale. Le réseau de solidarité que les femmes ont bâti dans le milieu musical depuis quelques années et la place que les compositrices occupent aujourd'hui témoignent de cette vitalité.
Keywords: 1900-1999; 1950-1959; 1960-1969; 1970-1979; 1980-1989; 1990-1999; amériques; discipline; femmes* artistes; femmes* compositrices; histoire; histoire des femmes*; périodes historiques; québec; ressource en ligne; régions géographiques; sciences humaines; thématiques; travail

Quand la violence parle du sexe : analyse du discours thérapeutique pour hommes violents - Letarte, Lise (Université du Québec à Montréal, 1998)
Keywords: IREF; amériques; discipline; hommes* violents; mémoires/thèses; québec; régions géographiques; sciences humaines; sexologie; thématiques; violences; violences contre les femmes*

Crise et mutation du dispositif de la différence des sexes : regard sociologique sur l'éclatement de la catégorie sexe - St-Hilaire, Colette (Les limites de l'identité sexuelle, 1998)
Keywords: 1900-1999; 1990-1999; amériques; cours; cycles supérieurs; différence des sexes; discipline; fem1000; fem7000; lit3220; premier cycle; périodes historiques; québec; régions géographiques; sciences humaines; sociologie

Lessons from the damned: queers, whores, and junkies respond to AIDS - Stoller, Nancy E. (Routledge, 1998)
"Lessons from the Damned challenges the notion that public health theories and official organizations have the greatest impact on the fight against AIDS. Instead, Stoller looks closely at the ways the most disenfranchised - the poor, people of color, drug users, gay men and lesbians, and women - have built social movements to fight the epidemic. Drawing upon extensive ethnographic research and the words of the activists themselves, as well as the literature of social movements and theories of bureaucracy, Stoller offers guidelines for dealing with diversity and conflict and also with both theoretical and practical perspectives on cross-community and international organizing."–BOOK JACKET.
Section: xvi, 175 pages : illustrations ; 24 cm
Keywords: 1900-1999; 1980-1989; 1990-1999; amériques; approches et analyses; capitalisme; care; cours; discipline; histoire et politique; hétérosexisme; justice sociale; militance; premier cycle; périodes historiques; régions géographiques; santé; sciences humaines; sexualité; sida; soc2014; sociologie; sofia; systèmes d'oppressions; thématiques; états-unis

L'art de la récupération des médias dans Médias et féminismes: minoritaires sans paroles - Yamani, Myriame el (Médias et féminismes: minoritaires sans paroles, 1998)
Les médias, s'ils informent, ne servent plus à communiquer. C'est pourquoi cet essai veut répondre à une double question : comment et pourquoi les minoritaires, et les femmes en particulier, s'ils prennent parfois la parole dans le champ médiatique en créant leurs propres journaux, ne peuvent pas la garder ? Comment et pourquoi les médias majoritaires ne rendent-ils pas compte de ces points de vue de minoritaires, en particulier lors d'événements qui les concernent ?
Section: 268 p. : ill. ; 22 cm
Keywords: 1900-1999; 1990-1999; amérique du nord; amériques; approches et analyses; canada; cours; discipline; médias; premier cycle; périodes historiques; québec; régions géographiques; sciences humaines; sexisme; systèmes d'oppressions; thématiques; travail; travail social; trs1205